Study And Design Of Robust Personal Sound Zones With Vast Using Low Rank Rirs - Bhattacharjee, Sankha Subhra; Shi, Liming; Ping, Guoli; Shen, Xiaoxiang; Christensen, Mads Grasboll (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2023)
The performance of sound zone control algorithms are known to degrade significantly with changes in acoustic conditions including perturbations of control microphones' positions. In this work, we study the feasibility and effectiveness of using low rank approximations of RIRs to calculate sound zone control filters, to improve the robustness of sound zone control algorithms to perturbations in the bright zone (BZ) microphones. For algorithm design, we consider the framework of variable span linear filter (VSLF) which allows a wide range of user selectivity between acoustic contrast (AC) and signal distortion (SD) trade off, including acoustic contrast control (ACC) and pressure matching (PM) methods as special cases. Detailed simulation study shows that above a certain rank of the variable span trade-off (VAST) filter, the proposed approach using low rank RIRs to derive the control filters provides higher AC compared to using full rank RIRs, when there are perturbations in BZ microphone positions.